Intangible Cultural Heritage Revitalization for Development and Tourism: The Case of Purulia Chhau Dance - Cardinale, Stefania (Material Culture Review, 2016)
UNESCO’s recent Conventions (2003 and 2005) take intangible heritage’s potential into account through integrating cultural expressions, practices and traditions into development frameworks. However, how this integration should happen in the realm of the practice and what impacts would result from it is crucial in defining also the safeguarding of intangible heritage. This article will investigate how the intangible cultural heritage (ICH) of Chhau dance of Purulia India, was accommodated in a development project. A critical examination of actors involved and actions of the project, through an actor-network perspective, will discuss what this meant in relation to the heritage. The article highlights that the actions of integrating intangible heritage into a development project framework translated into the revitalisation of the cultural element, considered an outdated cultural product in need of modernisation. To what extent has the traditional form of art changed in line with project and development expectations?